Characterizing natural and human-made features of sand dams in seasonal rivers of semi-arid regions in Kenya: A case of Kikuu sand river in Makueni County - Kigorwe, Faith Gaceri; Mworia, Kiogora; Muriungi, Robert; Mutuma, Benson; Matheka, Rosemary Mwende (African Journal of Science, Technology and Social Sciences, 2025)
Sand dams have been broadly used as water harvesting technologies in semi-arid regions and are constructed to enhance water accessibility and availability during the dry seasons. Sand dams’ effectiveness relies on proper interactions between natural and human-made features. However, there are few studies that have documented these characteristics and elements comprehensively. This study was aimed at identifying and describing natural and human-made features with a specific focus on sand dams along River Kikuu, Makueni county, Kenya. Field observational surveys were conducted on twenty-one (21) sand dam sites. Mapping was conducted using GIS with geospatial analysis done using QGIS software. The recorded elements were sand dam wall height, sand accumulation depths, and surrounding land cover characteristics. This study reports that studied sand dams varied in terms of dam heights, length, usage and adjacent natural as well as human modifications. Interestingly, sand dams along the Kikuu Sand River in Makueni county supported diverse farming systems and ecosystem functions, acting as a big source of livelihood for the community, enhancing food security. However, it was observed that some of the sand dams faced challenges such as reduced sand accumulation as a result of unregulated sand harvesting and structural dam wall damages. Because of this, there is need for regular monitoring of the sand dams, encouraging responsible sand harvesting, and supporting communities in adopting suitable water abstraction methods that match local needs and dam capacity. The study provides basis for informing future initiatives when it comes to planning, construction, placement, and comparisons of sand dams in other arid and semi-arid regions.